La citoyenneté européenne et le déficit démocratique - Stüttler, Ira (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1997)
The European citizenship and the democratic deficit are at the heart of the ongoing discussion about the European integration. Critics think that the possibility for the citizens to participate in the decision making process of the EU is not sufficient. In order to shed some light on this matter, the two concepts are examined under their different aspects. We emphasize not only their place in the larger context of the integration and the political situation in Europe but also the link between the two notions. This allows the conclusion that the European citizenship, because of its flexible and innovative character, should be the starting point in the search of an answer to the democratic deficit.